PELATIHAN PENYUSUNAN RPP BERBASIS SAINTIFIK PADA KELOMPOK KERJA GURU MI KABUPATEN SLEMAN - Izzatin Kamala (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
In the 2013 curriculum, a scientific approach is necessary for carrying out the learning process in all existing subjects. The scientific approach aims to facilitate students' learning like scientists—skills from the Syntax of this scientific approach help students construct knowledge. So teachers must understand how to implement a scientific approach to the learning process. This service activity is based on an analysis of teacher needs in designing scientific-based lesson plans. This service aims to optimize teacher competence in preparing learning implementation plans based on a scientific approach in the Sleman Regency Madrasah Ibtidaiyah Teacher Working Group. This community service activity starts with needs analysis, seminars on learning materials and scientific approaches, training, FGDs, and evaluations. The dedication results show that the teacher is enthusiastic about participating in the activity, and the teacher understands how to prepare a lesson plan based on a scientific approach oriented to student skills. The evaluation results show that the teacher wants a continuation of other training programs to increase the competency capacity of teachers.